2014
DOI: 10.5966/sctm.2013-0120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Wharton's Jelly Mesenchymal Stem Cell Paracrine Signaling on Keloid Fibroblasts

Abstract: Keloid scars are abnormal benign fibroproliferative tumors with high recurrence rates and no current efficacious treatment. Accumulating evidence suggests that human umbilical cord Wharton's jellyderived mesenchymal stem cells (WJ-MSCs) have antifibrotic properties. Paracrine signaling is considered one of the main underlying mechanisms behind the therapeutic effects of mesenchymal stem cells. However, the paracrine signaling effects of WJ-MSCs on keloids have not yet been reported. The aim of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 55 publications
0
61
0
Order By: Relevance
“…H&E and ORO staining of WAT as well as IHC staining of perilipin in liver were performed as described previously (15,16). The size of adipocytes was measured using ImageJ v1.48 (NIH).…”
Section: Hematoxylin and Eosin (Hande) Oro Immunohistochemical (Ihc) mentioning
confidence: 99%
“…H&E and ORO staining of WAT as well as IHC staining of perilipin in liver were performed as described previously (15,16). The size of adipocytes was measured using ImageJ v1.48 (NIH).…”
Section: Hematoxylin and Eosin (Hande) Oro Immunohistochemical (Ihc) mentioning
confidence: 99%
“…There is a substantial amount of literature which investigate the beneficial effects of cellular therapy with WJ-MSCs, alone or within a scaffold (Zebardast et al, 2010; Azari et al, 2011; Shohara et al, 2012; Arno et al, 2014; Fong et al, 2014; Ribeiro et al, 2014; Sabapathy et al, 2014). Emerging reports are showing the promising role of decellularized biological matrices for tissue repair (Boccafoschi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have elucidated the role of WJ-MSCs for various applications, such as for neurological disorders (Shalitin et al, 2003), kidney injury (Du et al, 2013), lung injury (Moodley et al, 2009), liver injury and cancer therapy (Sabapathy et al, 2014). We have recently reported that WJ-MSCs conditioned-medium with its secretome has positive effects on wound healing in vitro (Arno et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that human mesenchymal stem cells could have antifi brotic properties with paracrine signalling as one of the main underlying mechanisms behind their therapeutic eff ects. Th is therapeutical property might possibly be valuable when treating keloids and renal scarring [3,13]. Similarly experimental studies have shown the ability of the Wharton's jelly-derived mesenchymal stem cells to diff erentiate into adipocytelike cells with high chemokine secreting properties [2].…”
Section: Introductionmentioning
confidence: 99%